Pengaruh Likuiditas, Ukuran Perusahaan dan Struktur Modal terhadap Nilai Perusahaan pada Perusahaan Perbankan yang Terdaftar pada Bursa Efek Indonesia Periode 2020-2024 - Tia Fahda Absyari; Hasanudin Hasanudin (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
This study aims to analyze the effect of liquidity, firm size, and capital structure on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The background of this research lies in the crucial role of the banking sector in maintaining national economic stability and the need for investors to access financial information that accurately reflects a company’s value. Referring to signaling theory, financial reports are viewed as signals to investors regarding the firm’s prospects and performance. This study employs a quantitative method using secondary data from the annual financial reports of nine banks selected through purposive sampling, resulting in 45 observations. The independent variables include liquidity (Loan to Deposit Ratio), firm size (log of total assets), and capital structure (Debt to Equity Ratio), while the dependent variable is firm value measured by the Price to Book Value (PBV). Data analysis was conducted using panel data regression with SPSS. The results show that firm size has a significant positive effect on firm value, while liquidity and capital structure have no significant impact. Simultaneously, all three variables significantly affect firm value, with an Adjusted R² of 0.493. These findings highlight that effective asset management and optimal funding policies are key to enhancing the firm value of banking institutions in Indonesia.